Potential limitations of activity tracking devices in monitoring effects of treatment for sarcoidosis - Klein, Rebecca; Judson, Marc; Barkes, Briana; Maier, Lisa; Zeigler, Joyce; Culver, Daniel; Sweiss, Nadera; Chen, Edward; Hamzeh, Nabeel; Grutters, Jan; Valeyre, Dominique; Singh, Noopur; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Introduction: activity tracker device usage can help analyze the impact of disease state and therapy on patients in clinical practice. factors such as age, race, and gender may contribute to difficulties with using such technology. Objective: we evaluated the effect of age, race, and gender on the usability of the Fitbit OneTM activity tracking device in sarcoidosis patients and the impact of device on sarcoidosis patients’ activity. Method: patients participated in a six-month prospective study where were asked to wear a Fitbit OneTM activity tracker daily. device usage education was provided at study enrollment. weekly data download and submission reports to participating centers was required. patients were asked to complete a post-study questionnaire reviewing the motivation of the activity tracker on daily activity. Results: at three centers, 91 patients completed all study visits and the post study questionnaire with a mean age of 55 and 75% were female and 34% african american. accurate downloads occurred >75% of the time, regardless of age, race, or sex. results of the post-study questionnaire did not show a correlation between the likelihood of wearing the device and motivation to increase activity. Conclusion: using an activity tracking device to evaluate and/or correlated with quality of life (QOL) instruments may prove beneficial for gathering more data on patients. age, race, and gender did not contribute to differences in usability among sarcoidosis patients.